Application of Solid Expandable Tubulars in the Petroleum Industry (Rudarsko-geološko-naftni zbornik, 2022)
The development of solid expandable tubular (SET) technology and products (open hole liner, open hole clad, cased hole liner, liner hanger, internal casing patch, etc.) has enabled operators to plan well design in a new way and solve various problems that arise during drilling and exploitation on land and offshore. By including an expandable open hole liner, monobore open hole liner or monobore openhole clad in well design, it is possible to achieve a slim hole design and/or resolve unwanted situations that occur during the drilling of problem zones with minimal hole size reduction and reach hydrocarbon reserves which cannot be achieved economically by conventional technology. By installing an expandable cased hole liner or internal casing patch in production wells to cover the intervals of a corroded casing or to close old perforations, it is possible to extend the life cycle of a production well and increase the final hydrocarbon recovery and speed up the return on investment. The aim of the paper is to systematically review the relevant literature and give an overview of solid expandable tubular technology and its applications in the petroleum industry, as well as the cementing technology of open hole expandable liners. The available data for 21 case studies of SET application in onshore and offshore wells were analyzed in detail. Based on an extensive review of the literature and analyzed data, it can be concluded that SET technology is being successfully applied worldwide and that expandable liners with a diameter of 114.3 mm to 339.72 mm are being run in wells to ever greater depths (up to 5166 m) and in ever more extreme downhole conditions.